Identification Microorganism which have most stable ?-galactosidase Enzyme Based on Conformational Stability - Karina, Sheilla W; Agustina, Didin Wahyu; Mu'jizah, Elzafa Y; Sari, Aprilia K (Future Science, 2018)
Lactose intolerant is a condition which people can not hydrolyze lactose into glucose and galactoside. Recently Asia have 80% intolerant people in number. Body can hydrolyze and absorb lactose because they have ?-galactosidase enzyme in their digestive system which intolerant people did not have it. Dairy food industry such as milk, cheese, yoghurt and other low lactose usually adding ?-galactosidase enzyme using microorganism as source, but sometimes ?-galactosidase was isolated from microorganism has low stability. This project aim to find microorganisms that produce most stable ?-galactosidase and could be recommended for commercial industries to producing food with low lactose. This research use two step, Homology Modeling of ?-galactosidase enzyme from 10 microorganism by swiss model and calculates the free energy of unfolding using FoldX at Yasara software. Based on energy of protein stability the highest stability is Bacterioides thetainomicron and Eschericia coli. Keywords: ?-galactosidase, Homology modeling, Microorganism, Protein stability